Exploring the origins of neurodevelopmental proteasomopathies associated with cardiac malformations: are neural crest cells central to certain pathological mechanisms? - Vignard, Virginie; Baruteau, Alban-Elouen; Toutain, Bérénice; Mercier, Sandra; Isidor, Bertrand; Redon, Richard; Schott, Jean-Jacques; Küry, Sébastien; Bézieau, Stéphane; Monsoro-Burq, Anne H.; Ebstein, Frédéric (Frontiers in Cell and Developmental Biology, 2024)
Neurodevelopmental proteasomopathies constitute a recently defined class of rare Mendelian disorders, arising from genomic alterations in proteasome-related genes. These alterations result in the dysfunction of proteasomes, which are multi-subunit protein complexes essential for maintaining cellular protein homeostasis. The clinical phenotype of these diseases manifests as a syndromic association involving impaired neural development and multisystem abnormalities, notably craniofacial anomalies and malformations of the cardiac outflow tract (OFT). These observations imply suggest that proteasome loss-of-function variants primarily affect a specific embryonic cell types which serves as the origins for both craniofacial structures and the conotruncal region portion of the heart. In this hypothesis article, we propose that neural crest cells (NCCs), a highly multipotent cell population, which generates craniofacial skeleton, mesenchyme as well as the OFT of the heart, in addition to many other derivatives, would exhibit a distinctive vulnerability to protein homeostasis perturbations. Herein, we introduce the diverse cellular compensatory pathways activated in response to protein homeostasis disruption and explore their potential implications for NCC physiology. Altogether, the paper advocates for investigating proteasome biology within NCCs and their early cranial and cardiac derivatives, offering a rationale for future exploration and laying the initial groundwork for therapeutic considerations.